Nominal Modification in Italian Sign Language - Mantovan, Lara (Sign Languages and Deaf Communities [SLDC], 2017)
This book presents a syntactic analysis of nominal expressions in Italian Sign Language combining three different theoretical dimensions of inquiry: linguistic typology, generative linguistics, and sociolinguistics. Three empirical studies are presented: the distribution of nominal modifiers, the duration of nominal modifiers, and the syntax of cardinal numbers.